실리카-그라파이트 이원 충진제를 이용한 SBR 컴파운드의 성질 - 신지항; Ji Hang Shin; A M Shanmugharaj; 이평찬; Pyoung Chan Lee; 정선경; Sun Kyung Jeoung; 류승훈; Sung Hun Ryu (Elastomers and composites, 2014)
실리카 입자에 팽창흑연을 그라프트 시킴으로 카본코팅을 실시하였으며, 이를 확인하기 위하여 FT-IR, TGA, XPS 그리고 TEM 분석을 실시하였다. 코팅된 흑연의 결정특성은 XRD를 이용하여 확인하였으며, 카본 코팅된 실리카가 SBR 컴파운드의 유변학적 그리고 기계적 성질에 미치는 영향에 대하여 살펴보았다. 카본 코팅된 실리카를 이용한 경우 순수 실리카를 이용한 경우에 비하여 SBR 컴파운드의 유변학적 그리고 기계적 성질이 크게 향상됨을 알 수 있었다. 이러한 현상은 평형팽창비율과 bound 고무 양 변화로도 확인 할 수 있었다. Carbon coating on silica particles is done by grafting expanded graphite on the silica aggregates. Successful coating of carbon is corroborated using FT-IR, TGA, XPS and TEM. Crystalline nature of coated graphite is corroborated using XRD. Influence of carbon coated silica particles on rheometric and mechanical properties of SBR composites are investigated. Carbon coated silica particles showed significant improvement in rheometric and mechanical properties, when compared to pristine silica filled system corroborating higher polymer-filler adhesion. This fact was further supported by bound rubber content and equilibrium swelling ratios of unvulcanized and vulcanized SBR composites.